A proteção social nos serviços de saúde voltados à pessoa idosa em Céu Azul - PR - Floriano, Tânia (2021)
The dissertation entitled: Social Protection in Health Services Aimed at the Elderly in Céu Azul – PR places the analysis in the context of the Brazilian State, permeated by the neoliberal trend of commodification of social policies, including the Health Policy. , in addition to not ensuring the Health Policy from the perspective of guaranteeing rights, it weakens the implementation of health services. Like other users of the Health Policy, Brazilian elderly people face numerous difficulties in accessing, quality and comprehensive health care for most of their lives, especially elderly people, classified by the Health Policy as 'weak risk', hereinafter referred to as 'elderly person with frail risk classification', who are bedridden and/or domiciled. This justifies the need to analyze the effectiveness of social protection in health services aimed at the elderly, with a fragile risk classification, served by the Municipal Health Department of Céu Azul – PR. Therefore, the following guiding question was defined: What are the difficulties faced by the families of elderly people, with a fragile risk classification, in health care in primary care? And from this, the general objective and specific objectives were defined, with the general objective being: To identify the difficulties faced by the families of elderly people, with fragile risk classification in health care in primary care. And the specific objectives: Contextualize the National Health Policy for the Elderly (PNSPI); Identify the Health Care Policy for the elderly in the western region of Paraná and in Céu Azul-PR; Identify the Health Care Network for the elderly in Céu Azul-PR, locating services for the elderly with a fragile risk classification; To analyze how the care of elderly people with a fragile risk classification is carried out in the family environment; Analyze the facilities and difficulties in accessing the network of municipal and regional health services and intersectoral policies. Regarding the research methodology, we sought to analyze the object of this study as a totality of reality from the contradictory mediations that permeate the PNSPI, inserted in the correlation of forces expressed by the market, the State and civil society. It is an approximate, exploratory research with qualitative methodological aspects. To build the research, bibliographical surveys and selections, documental research and the interview were carried out, which had a semi-structured script. This dissertation is composed of three chapters with the titles: The first, "Social Question" and National Health Policy for the Elderly, the second: Problematizing the Classification of Frail Elderly in Health Services and the third: Social Protection in Health Services Health Aimed at the Elderly in Céu Azul - PR. The results of the research and data analysis demonstrate that elderly people with frail risk classification attended by the Health Policy face fragile and fragmented services, which compromises the principle of comprehensive health, violates the achievements of the SUS and the Policy National Health Care for the Elderly (PNSPI), thus not effecting the social protection guaranteed in the Federal Constitution of 1988. Therefore, it is proven that the current economic system does not prioritize the materialization of the elderly person's right to health, as it reinforces the continuation of acute and immediate actions, which compromise the quality of health services aimed at this population segment.